Patient Selection in Plastic Surgery: Recognizing Body Dysmorphic Disorder - Cihan Sahin; Onat Yilmaz; Yalcin Bayram; Huseyin Karagoz; Celalettin Sever; Yalcin Kulahci; Alpay Ates (Archives of Clinical and Experimental Surgery, 2013)
Plastic surgery is a branch of medicine that provides significant improvements to the people with positive changes. But first of all, this branch has a characteristic which requires analysing patients' psychological situation very carefully. Plastic surgeons are often confronted by patients with mental disorders seeking aesthetic surgery. It is imperative for surgeons to recognize possible underlying psychiatric illnesses. Common psychiatric conditions seen in cosmetic surgery patients include body dysmorphic disorder (BDD), narcissistic personality disorder and histrionic personality disorders. BDD is of particular importance to plastic surgeons. Because outrageous dissatisfaction with one's appearance may conceal psychopathologic traits that are not always easily recognizable, and which, if neglected, may result in serious iatrogenic and medicolegal consequences, we hope that this paper will help plastic surgeons in ultimately preventing patient and surgeon dissatisfaction within the population of patients with psychiatric disorders, and should recognize the diagnostic features of body dysmorphic disorder and screen psychologically unstable patients who may never be satisfied with surgery. [Arch Clin Exp Surg 2013; 2(2.000): 109-115]